Bridging Efficiency within Multinuclear Homogeneous Catalysts in the Photocatalytic Reduction of Carbon Dioxide. Issue 21 (11th September 2015) - Meister, Simon; Reithmeier, Richard O.; Ogrodnik, Alexander; Rieger, Bernhard
Abstract: A trinuclear complex consisting of one [Ru(dmb)3 ] 2+ (dmb=4, 4′‐dimethyl‐2, 2′‐bipyridine) (Ru ) and two [Re(dmb)(CO)3 Cl] (Re ) building blocks, [Re(CO)3 Cl(dmb−dmb)Ru(dmb)(dmb−dmb)Re(CO)3 Cl](PF6 )2 (Re −Ru −Re ), is presented. Photophysical properties ofRe −Ru −Re and the individual components with different or no covalent linkages are thoroughly investigated and compared. To elucidate the role of the single covalent bonds, photocatalytic reduction of CO2 is performed with the trinuclear complex and a series of model systems featuring systematic absence of linkages between the metal centers. Photoluminescence spectra and quantum yields reveal efficient energy transfer from the excited state ofRe toRu if these fragments are covalently linked. Moreover, intramolecular electron transfer from the one‐electron reduced species ofRu toRe occurs if there is covalent bonding, leading to a higher photostability and thus the highest turnover number in photocatalytic CO2 reduction of 199 for the trinuclear complexRe −Ru −Re within the systems under investigation. Optimized experimental conditions reveal the highest turnover number (315) reported to date for Re I /Ru II ‐based homogeneous catalysts in photocatalytic CO2 reduction. Abstract : The best things come in threes : A trinuclear Re I /Ru II complex is presented with high photostability. We reveal a turnover number of 315, the highest reported to date for a Re I /Ru II ‐based homogeneous catalyst in photocatalytic CO2 reduction. D=electron donor.